2008
DOI: 10.1111/j.1471-4159.2008.05218.x
|View full text |Cite
|
Sign up to set email alerts
|

The Akt signaling pathway contributes to postconditioning’s protection against stroke; the protection is associated with the MAPK and PKC pathways

Abstract: We previously reported that ischemic postconditioning with a series of mechanical interruptions of reperfusion reduced infarct volume 2 days after focal ischemia in rats. Here, we extend this data by examining long‐term protection and exploring underlying mechanisms involving the Akt, mitogen‐activated protein kinase (MAPK) and protein kinase C (PKC) signaling pathways. Post‐conditioning reduced infarct and improved behavioral function assessed 30 days after stroke. Additionally, postconditioning increased lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
171
1
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 154 publications
(188 citation statements)
references
References 50 publications
15
171
1
1
Order By: Relevance
“…1 To date, early brain ischemic postconditioning has been first reported in focal ischemia, [3][4][5] then delayed postconditioning against focal 6 and in global ischemia. 7 We have previously shown that hypoxic preconditioning (8% O 2 , 1 hour) performed 24 hours before focal cerebral ischemia in adult mice protects the brain.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…1 To date, early brain ischemic postconditioning has been first reported in focal ischemia, [3][4][5] then delayed postconditioning against focal 6 and in global ischemia. 7 We have previously shown that hypoxic preconditioning (8% O 2 , 1 hour) performed 24 hours before focal cerebral ischemia in adult mice protects the brain.…”
Section: Discussionmentioning
confidence: 99%
“…The protection has been associated with the activation of the protein kinase Akt. 4,5 Besides ischemic postconditioning, the existence of hypoxic postconditioning has been described in the heart 8 but not in the brain neither in vivo nor in vitro.Therefore, the aim of this study was to search for the existence of hypoxic postconditioning against focal cerebral ischemia in the mouse. We show that a delayed application of chronic intermittent hypoxia after ischemia led to a significant neuroprotection assessed by T2-weighted MRI.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Abundant GSK-3 in the brain is also a negative regulatory factor of signaling cascades, including PI3K/Akt (7). GSK-3β can be deactivated through Akt-mediated phosphorylation at serine 9, which produces antiapoptotic effects (8,9). During GSK-3β phosphorylation, β-catenin dissociates from the anaphase-promoting complex, enters the nucleus and potentiates the transcription of Wnt target genes, thereby promoting cell proliferation and inhibiting apoptosis (10)(11)(12).…”
Section: Introductionmentioning
confidence: 99%